Nilai-Nilai Moral dan Spiritual; Pengaruh Wisata Religi Terhadap Peluang Ekonomi Rakyat - Ieke Sartika Iriany; Rostiena Pasciana; Mulyaningsih Mulyaningsih; Ismira Febrina (Tourism Scientific Journal, 2021)
The tourists invasion to the sanctuary of the Islam spreaders, it is the social dynamics to strenghten faith. West Java is one of the provinces that has the potential for religious tourism which is much loved by the Indonesian people. This attracts researchers to examine more deeply the relationship between religious tourism and people's economic opportunities. This study aims to describe and analyze the influence of religious tourism on the people's economic opportunities. Religious tourism in West Java are mostly visited. In this situation, people’s economic opportunities can be captured by the local people, such as the souvenirs and flowers sellers. This research uses a quantitative approach to find out how significant the influence of Religious Tourism on the people's economic opportunities is and analyze it through the sociology of religion. The population in this study are people who work as traders who sell at the research location; with a sample of 59 people obtained through simple random cluster sampling. Based on the results of the analysis that there is a influence of religious tourism on the community economic opportunities, which is equal to 32.15%. Meanwhile, 67, 85% were influenced by other factors not examined in this study. From the effectiveness of religious sociology, and Parson's theory as a social system, which is explored through analysis of Adaptation, Goal Attainment, integration and Latent Pattern Maintenance is very relevant. seizing people's economic opportunities by adapting tourism elements, as well as trying to carry out cultural and religious attractions, such as solemn and silent prayer rituals, in accordance with tourist expectations. This pilgrimage tourism activity can integrate with tourist destinations and can carry out the maintenance of local cultural patterns. However, to increase the potential for pilgrimage tourism, it is still necessary to maintain a better environment and order.